Case report: Stereotactic MR-guided adaptive radiotherapy for inoperable urothelial carcinoma at the renal pelvis - Thaweerat, Wajana; Dankulchai, Pittaya (Frontiers in Oncology, 2024)
We report the case of an 87-year-old woman with upper tract urothelial carcinoma at the left renal pelvis. She received stereotactic body radiotherapy of 35 Gy in five fractions for palliative treatment of hematuria that was delivered by a 1.5-T magnetic resonance (MR) imaging-guided linear accelerator. Her symptom was relieved after treatment, and posttreatment imaging revealed a complete response of the primary tumor. Thus, this case showed that stereotactic MR-guided radiotherapy could be an appealing option for inoperable patients although radiotherapy is infrequently mentioned in the current treatment guideline of upper tract urothelial carcinoma. Daily adaptive planning from MR images obtained before treatment could improve the target dose and minimize the organ at risk dose. This may lead to a decrease in radiation adverse effects including worsening renal function due to the renal pelvis tumor’s proximity to the kidney.